Development of Mobile Learning Media for Physical Education on Volleyball Games at Junior High School in Lubuklinggau - Pulka, Ismail (Journal of Social Work and Science Education, 2023)
The purpose of this study is to develop learning products in the form of mobile learning media development of physical education learning material for volleyball games at the junior high school level in Lubuklinggau motivated by the lack of maximum media development applied to volleyball game material at the junior high school level in Lubuklinggau, so that there needs to be innovation in the use of learning media to create a pleasant learning atmosphere for students when learning physical education, especially volleyball game material. This study aims to determine that the material and learning media for mobile learning physical education material for volleyball games can be applied in junior high schools in Lubuklinggau. This research is research with the development method (R&D), the instruments in this study used questionnaires and interviews. The results of validation by linguists on mobile learning media for physical education of volleyball game material with a percentage of 92.85% including criteria Very Good. The results of validation by material experts on mobile learning media for physical education of volleyball game material with a percentage of 96.42% including criteria Very Good. The results of validation by media experts obtained an overall score with a percentage of 91.25% including the criteria Very Good. The results of small group student responses were obtained with a percentage of 90.5% including the criteria Very Good. While the results of large group responses were obtained with a percentage of 84.44% including the criteria Good.